The Model of Internalizing Islamic Values Based on Local Wisdom in Islamic Religious Education (PAI) Learning at SMPN 1 Keruak - Nasri (Formad English Foundation NTB Jakarta, 2025)
This study is motivated by the limited empirical research on the integration of Islamic values and local wisdom within Islamic Religious Education (PAI) in public secondary schools, despite its significant role in shaping students’ character and religious attitudes in multicultural contexts. The study aims to identify the forms of Islamic values internalized through PAI learning, examine teachers’ strategies in integrating Islamic values through local wisdom, and analyze the impact of this internalization on students’ character development and religious behavior at SMPN 1 Keruak. The research adopts a qualitative case study design, involving 27 participants consisting of PAI teachers, school leaders, and students selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and documentation analysis conducted from November to December 2025. The data were analyzed using thematic analysis to identify recurring patterns, meanings, and relationships across data sources. The findings reveal that Islamic values related to Akidah, Sharia, and Akhlak are systematically internalized through culturally responsive pedagogical strategies. Teachers employ integrated approaches including value alignment with local wisdom, contextualized instruction, participatory learning, role modeling and habituation, as well as critical cultural analysis. These strategies contribute to the development of students’ religious discipline, social solidarity, respectful behavior, environmental awareness, and social empathy. The results align with character education and culturally responsive pedagogy theories, emphasizing the importance of contextual learning in value formation. The study concludes that integrating Islamic values through local wisdom strengthens the effectiveness and sustainability of character education in public schools. The findings contribute theoretically to Islamic education and value internalization studies and offer practical implications for educators and policymakers in designing culturally grounded PAI learning models. Future research is recommended to employ comparative and longitudinal approaches across diverse educational settings.